Preparation and evaluation of a set of bis(methoxycarbonylmethylthio) heteroquinones as CDC25B phosphatase inhibitors - Besset, Tatiana; Braud, Emmanuelle; Jarray, Rafika; Garbay, Christiane; Kolb, Stephanie; Leo, Pierre-Marc; Morin, Christophe (European Journal of Chemistry, 2011)
A set of new heteroquinone derivatives bearing two methoxycarbonylmethylthio groups on the benzoquinone ring were synthesized and evaluated for CDC25B phosphatase inhibitory activity. All compounds inhibited the enzyme with IC50 values in the micromolar range regardless of the size and heteroatoms constituting the heterocycle fused to the quinone ring. Moreover, these quinonoid-based compounds showed moderate antiproliferative activity toward two cancer cell lines (HeLa and MiaPaca-2). These results provide additional data for CDC25 inhibition by quinone-type derivatives and highlight the importance of substituents on the quinonic moiety.